A Case of Dysgraphia after Cerebellar Infarction Where Functional NIRS Guided the Task Aimed at Activating the Hypoperfused Region. (24th June 2021) - Fujii, Mutsumi; Tanigo, Kazumi; Yamamoto, Hirokazu; Kikugawa, Keijyu; Shirakawa, Masayuki; Ohgushi, Miki; Chin, Takaaki
Abstract : Background . Linguistic impairment following cerebellar lesions is characterized by a marked cerebellocerebral diaschisis with decreased perfusion in the left cerebral hemisphere. Case . We report on a 60-year-old right-handed French chef who presented with linguistic deficits following a right cerebellar infarction. Neurolinguistic examinations in the acute phase showed impaired graphomotor planning, especially for kanji (Japanese morphograms). Despite the absence of any structural damage to the supratentorial brain regions, a quantitative 123 I-IMP SPECT study revealed a relative hypoperfusion, mainly around the left posterior middle temporal gyrus, considered to be a crossed cerebellar-cerebral diaschisis. We performed functional near-infrared spectroscopy (fNIRS) and observed that a picture card task could increase blood perfusion in the affected area. This task was as follows: once he saw a picture card depicting a dish, the patient had to list the ingredients that make up the dish. For example, he had to name vegetables, meat, and spices upon seeing a "curry" picture card. We added this task to his daily speech-hearing therapy regimen. In the chronic phase, we confirmed symptom amelioration in linguistic performance-paralleled reduction in the level of hypoperfusion on SPECT study. Discussion . This case is the first report of an fNIRS approach used to evaluate evidence-based prospective speech-hearing tasks by observing blood flow to the hypoperfused area of the cerebral cortex surface.